The effect of oxygen deprivation mask training on speed endurance, maximum oxygen consumption, and 800m performance in the youth category. - Khodair, Asst.L.Hisham Hassan; Jawad, L.Dr.Saad Alawi (Sulaimani Journal for Humanities, 2026)
This research aims to develop training using oxygen deprivation masks to improve speed endurance, maximum oxygen consumption, and the ability to complete the 800m race. It also seeks to identify the effect of oxygen deprivation mask training on these performance levels. The research hypothesis is that oxygen deprivation mask training has a positive effect on improving speed endurance, maximum oxygen consumption, and the ability to complete the 800m race. There was a difference in the impact of training between the two groups (control and experimental) on developing speed endurance, VO2max (maximum oxygen consumption), and 800m performance, favoring the experimental group (oxygen deficiency masks). The researchers used the experimental method, one of the most widely used scientific research methods in the field of sports, because it is based on direct and realistic interaction with various phenomena and rests on two fundamental pillars: observation and experimentation of various types. The choice of method depends primarily on the nature of the problem to be solved. Therefore, the researcher used the experimental method with a two-group equivalent (control and experimental) design with pre- and post-tests, as it was suitable for the nature of the research. Using a suitable experimental design is important in writing the research because it helps in obtaining answers to the research hypotheses and also facilitates experimental control. The research population was defined as (10) runners from the Middle Euphrates governorates in the 5000m race, youth and adult category. The research sample was selected using a census method, meaning that the population was the same as the research sample, i.e., the sample percentage was 100%. The sample was randomly divided (by lottery) into two groups. A control and experimental group, each group consisting of (5 runners), was used by the researchers to homogenize the research sample in terms of (height, mass, training age, and chronological age) because of their effect on the dependent research variables, in order to control and eliminate their effect, as they share an effect with the independent indicators, through the use of the statistical law of the coefficient of variation.